Effects of Highlighting Fluency and Dysfluency in Stutterer - Mahapatra, Satyanarayana (Journal of All India Institute of Speech and Hearing)
Flanagan, Goldiamond and Azrin (1958) were the first ones who described operant control over stuttering. The application of these operant principles for the treatment of stuttering has been principally in two : ways (l) punishment or use of aversive contingencies for the unwanted dysfluencies, (2) reward or use of positive non-aversive contingencies with the fluency. Some authors however used both punishment for dysfluencies and rewards for fluency.